Chronic inflammation as a potential mediator between phthalate exposure and depressive symptoms - Chao Bao; Jia Lv; Jian-rong Chen; Guo-zhang Wei; Nuo Liu; Yi-tao Wang; Zheng Ding; Wei-bo Liu; Xiu-de Li; Hong-juan Cao; Jie Sheng; Kai-yong Liu; et al. (Ecotoxicology and Environmental Safety, 2022)
Background: A few studies have reported phthalate exposure as a risk factor for depressive symptoms, but the results have been inconsistent. Whether chronic inflammation mediates the relationship between phthalates (PAEs) and depressive symptoms remains unclear. In this study, we establish mediating models of inflammatory factors and explore the mediating role of chronic inflammation in the association between PAEs exposure and depressive symptoms. Methods: The sample included 989 participants from the Study on Health and Environment of the Elderly in Lu'an City, Anhui Province. Geriatric depression scale (GDS-30) was used to screen depressive symptoms of the elderly. The levels of seven kinds of PAEs in urine samples and four inflammatory factors in serum of the elderly were measured. To establish the mediating effect of inflammatory factors to explore the potential effect of PAEs exposure on the increased odds of depressive symptoms. Results: Adjusted for multiple variables, the highest tertiles of Mono (2-ethylhexyl) phthalate (MEHP) (95%CI = 1.051–2.112), Mono benzyl phthalate (MBzP) (95%CI = 1.016–2.082) and Mono butyl phthalate (MBP) (95%CI = 1.102–2.262) were positively correlated with depressive symptoms. The mediating effect of IL-6 and generalized inflammation factor between MEHP exposure and depressive symptoms were 15.96% (95%CI=0.0288–0.1971) and 14.25% (95%CI = 0.0167–0.1899). Conclusions: High levels of MEHP, MBzP and MBP increased the odds of depressive symptoms in the elderly, and chronic inflammation had a partial mediating effect on the increased odds of depressive symptoms due to MEHP exposure.